La fluidez conceptual en la interlengua escrita de aprendientes alemanes de español como lengua extranjera - Gallego, Carmen Mateo (Linguistik Online, 2018)
This paper focuses on the written interlanguage of German college students studying Spanish as a Foreign Language in four different levels (A2-C1). In order to observe the evolution of conceptual fluency, a total number of sixty participants wrote an essay about their Spanish studies without previous instruction on the Theory of Conceptual Metaphor (Lakoff/Johnson 1980). The metaphorical density index was measured with special attention paid to the differences and similarities between the German and Spanish semantic conceptual systems and the metaphors used in each stage of learning. The results show that the L1 plays a fundamental role in the typology of metaphors, while quantitative factors such as the metaphorical density index can also vary depending on the target language and the topics of the essays. Therefore, conventional metaphors play a fundamental role in foreign language learning, as the most significant examples in terms of lack of conceptual fluency have been caused by copying linguistic structures from conventional German metaphors into the target language.